Design and creation of a web-based coffee machine sales Information System at Pt. Nutraco Mesindotama - Zidan, Muhammad; Fauziyah, Fauziyah; Zulkarnain, Iskandar (Journal of Engineering, Technology and Computing (JETCom), 2024)
PT Nutraco Mesindotama is a distributor of coffee machines with a wide range of automatic and semi-automatic coffee machines for homes, offices, cafes and hotels. The current problem at PT Nutraco Mesindotama is that there are frequent errors in recording sales and purchase transaction information. Inaccurate information regarding the availability of stock items is caused by the negligence of the sales department in recording the number of items that have been sold into the report book. To deal with these problems, a web-based coffee machine sales information system was designed and built using Unified Modeling Language (UML) system modeling, PHP as a programming language and MySQL as a database, so that the process of recording sales transactions and stock information becomes easier to use, accurate, and integrated.